Paroxysmal Neuralgia in Pediatric Population- A Diagnostic Dilemma for Physicians and Dental Practioners - Dubey, A; Mujoo, S; Sakarde, SB; Dubey, AK (Kathmandu University Medical Journal, 2014)
Paroxysmal neuralgia is relatively uncommon in children. Neuropathic orofacial pain is a challenge for the clinician, as no obvious dental pathology exists either clinically or radiographically. Dentist and physician should be able to recognize the characteristics of neuropathic pain so as to correctly diagnose these conditions hence avoid unnecessary dental intervention. This article reviews the conditions with paroxysmal neuralgia in children and available treatment strategies. DOI: http://dx.doi.org/10.3126/kumj.v10i4.11000 Kathmandu Univ Med J 2012;10(4):74-77